Arator: Historia Apostolica. Translated with an introduction and notes by Richard Hillier - Woods, David (The journal of theological studies, 2023)
Arator enjoyed a varied career in Italy during the first half of the sixth century. Born probably in Liguria c.490, orphaned early and placed under the guardianship of bishop Laurentius of Milan (c.490-511), he received his early education in Milan, served as an advocate in Ravenna, rose high there in the service of successive kings of the Ostrogoths, Theoderic (493-526) and Athalaric (526-34), was in Rome by 537, and served as sub-deacon under Pope Vigilius (537-55). His claim to fame lies in his composition of the Historia Apostolica, an epic poem that retells the story of the Acts of the Apostles and offers a detailed allegorical interpretation of the same. He formally presented a copy of this work to Pope Vigilius in the basilica of St Peter on the Vatican Hill at Rome in front of a large crowd of bishops and other clergy on 6 April 544. He also sent a copy to his former classmate Parthenius who was serving as magister officiorum under King Theudebert I of Austrasia (533-48), and to Florianus, abbot of the monastery of Romenum. His orthodoxy, poetic proficiency, and skill at self-promotion ensured that his work enjoyed wide circulation throughout the medieval period, influencing the works of perhaps more famous scholars such as Venantius Fortunatus (d. 610), the Venerable Bede (d. 735), and Hrabanus Maurus (d. 856), to name but a few.